2013
DOI: 10.1523/jneurosci.4293-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Global Similarity and Pattern Separation in the Human Medial Temporal Lobe Predict Subsequent Memory

Abstract: Intense debate surrounds the role of medial temporal lobe (MTL) structures in recognition memory. Using high-resolution fMRI and analyses of pattern similarity in humans, we examined the encoding computations subserved by MTL subregions. Specifically, we tested the theory that MTL cortex supports memory by encoding overlapping representations, whereas hippocampus supports memory by encoding pattern-separated representations. Consistent with this view, the relationship between encoding pattern similarity and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
224
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(252 citation statements)
references
References 58 publications
21
224
3
Order By: Relevance
“…First, results from both rodent (33) and human research (34) demonstrate that false memories can be established as memory "engrams" within the hippocampus through artificial manipulation or reconsolidation processes. Second, recent studies have shown that recognition memory performance can be driven by a dynamic similarity-based computation within the medial temporal lobe at retrieval (35,36). It is likely that both sets of processes interact with the semantic representations in the TP to produce semantic false memories (3, 6, 37).…”
Section: Discussionmentioning
confidence: 99%
“…First, results from both rodent (33) and human research (34) demonstrate that false memories can be established as memory "engrams" within the hippocampus through artificial manipulation or reconsolidation processes. Second, recent studies have shown that recognition memory performance can be driven by a dynamic similarity-based computation within the medial temporal lobe at retrieval (35,36). It is likely that both sets of processes interact with the semantic representations in the TP to produce semantic false memories (3, 6, 37).…”
Section: Discussionmentioning
confidence: 99%
“…Is it necessary to consider attentional states to predict memory from the hippocampus during encoding? To assess the selectivity of our findings to the state-template match variable, we examined two additional variables that have been linked to encoding in prior subsequent memory studies: (i) patterns of activity without respect to attentional state (37)(38)(39), and (ii) the overall level of univariate activity (5,23,40).…”
Section: Predicting Memory From the Attentional State Of The Hippocampusmentioning
confidence: 99%
“…This overlapping representation should interfere with the original representation in memory, in some cases leading to difficulty in correctly rejecting the lure image. Based on prior work in humans (13)(14)(15), it is thought that correct rejection of these similar lures depends at least in part on successful resolution of this interference in the hippocampus.…”
Section: Significancementioning
confidence: 99%
“…This computation is widely thought to occur as a function of sparse firing patterns of granule cells of the hippocampal dentate gyrus (DG), which form powerful mossy fiber synapses with large numbers of pyramidal cells in subregion CA3 (3)(4)(5)(6). A critical role for the DG in orthogonalizing interfering inputs has been demonstrated in animal studies by using lesions (7)(8)(9), NMDA receptor knockouts (10), electrophysiological recordings (11,12), and human functional MRI (13)(14)(15).…”
mentioning
confidence: 99%